MAKING AN ANTISEPTIC CREAM FROM RED BISH LEAF EXTRAK (PIPER CROCATUM RUIZ & PAV) - Hanindiya, Beta; Bahmani-Oskooee, Mohsen; Kurniawan, Hendri; Sumule, Arsiaty; Delfaheda, Yulia (Universitas Efarina, 2019)
Red betel is a plant that has many benefits as a medicinal plant, red betel plant is a source of traditional medicinal ingredients that are widely used from generation to generation. some antiseptics inhibit growth against Escherichia coli and Staphylococcus aureus. The research stages used included the collection and processing of samples, the characteristics of simplicia, phytochemical screening, the manufacture of ethanol extracts by maceration using 96% ethanol solvent, and the antibacterial activity test using the agar diffusion method using a paper barrier against Escherichia coli and Staphylococcus aureus by measuring the zone diameter. inhibit bacterial growth. The results of the examination of the characteristics of the red betel leaf simplicia powder showed total ash content of 9.65%, acid insoluble ash content of 1.20%. The results of the phytochemical screening examination contained chemical compounds of the phlovonoid group, saponin tannins, and triterpenoid streroids. The ethanol extract of red betel leaf has antibacterial activity against Escherichia coli and Staphylococcus aereus. The results of the antibacterial activity test for the ethanol extract of red betel leaf against Escherichia coli bacteria obtained KHM 100 mg/ml with a diameter of 25 mm from Staphylococcus gereus and obtained KHM 100 mg/ml with a diameter of 28 mm.